Reducing criminal recidivism with an enhanced day reporting center for probationers with mental illness. Issue 2 (17th February 2016) - Carr, W. Amory; Baker, Amy Nicole; Cassidy, James J.
ABSTRACT: Offenders with mental illness (OMI) represent a significant portion of the community corrections population (e.g., probation, parole) for whom innovative interventions that target criminal recidivism must be assessed. This retrospective, quasi-experimental study compared recidivism outcomes of OMI probationers discharged from an enhanced day reporting center (DRC) with a comparable sample of probationers matched by propensity score ( N  = 227). Cox proportional hazard regressions demonstrated that participants of the DRC were significantly less likely to be reconvicted after discharge from the program, 2(2, N  = 227) = 5.9, p  = .02. Furthermore, DRC completers demonstrated a 40% reduction in risk of reconviction postdischarge compared to the matched sample.